2021
DOI: 10.2147/nrr.s331137
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Related Fears Among Mzuzu University’s Nursing Students During Clinical Practice

Abstract: Purpose: Clinical practice during pandemics is known to bring additional fears to nursing students. The purpose of this study was to explore fears of Mzuzu University's nursing students nurses regarding resumption of clinical practice amidst the Coronavirus disease (COVID-19) pandemic. Methods: The study used a qualitative approach employing a descriptive phenomenological design. Mzuzu University Research Ethics Committee (MZUNIREC) approved the study and issued MZUNIREC/DOR/20/06 as approval number. An indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This finding is in agreement with another study in which participants narrated that the shortage of equipment and supplies in the clinical area aroused fear in them. 12 In the present study, participants reported a lack of patient-oriented teaching due to the fear of spreading the disease. Similarly, another study reported that students used avoidance strategies due to fear of contracting COVID while in clinical practice.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This finding is in agreement with another study in which participants narrated that the shortage of equipment and supplies in the clinical area aroused fear in them. 12 In the present study, participants reported a lack of patient-oriented teaching due to the fear of spreading the disease. Similarly, another study reported that students used avoidance strategies due to fear of contracting COVID while in clinical practice.…”
Section: Discussionmentioning
confidence: 60%
“…Similar narrations were identified in which participants feared they would face stigma and discrimination by the community. 12 Students reported a shortage of Personal Protective Equipment during clinical posting. This finding is in agreement with another study in which participants narrated that the shortage of equipment and supplies in the clinical area aroused fear in them.…”
Section: Discussionmentioning
confidence: 99%
“…Between April and September 2020, during a partial lockdown in Malawi, there was a rise in suicide cases, most of which were attributed to financial hardship due to a slowdown in economic activities [ 44 ]. Mental health challenges were also observed in students who feared future employment uncertainties and the effect of COVID‐19 upon completion of their studies [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a 5‐month long school closure of schools at the peak of the pandemic resulted in increased school dropouts [ 13 ]. A COVID‐19 rapid assessment on teenage pregnancies and early marriages led by the Malawi Government reported over 40,000 teenage pregnancies between March and July 2020, an 11% increase from the same period in 2019 [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%